Case report: Dysphonia associated with high-dose cytarabine therapy - Ling Ma; Niya Huang; Haixi Zhang; Jia Liu; Zhiqing Zhang (Frontiers in Pharmacology)
Cytarabine is widely used in the treatment of hematological malignancies. Its common toxicities include myelosuppression and gastrointestinal disturbances. Additionally, it can cause central nervous system (CNS) symptoms, which include hoarseness, ataxic tremor, ataxic gait, nystagmus, dysmetria, and dysdiadochokinesia. In this article, we present the first case report of dysphonia, absent of CNS symptoms, induced by high-dose cytarabine (HiDAC) in a patient with acute myeloid leukemia. The patient’s voice began to change 3 days following the first cycle of HiDAC chemotherapy, and dysphonia recurred upon the reintroduction of HiDAC. To rule out other potential causes, a thorough examination and detailed medical history review were conducted, excluding factors such as vocal abuse, infection, effects of other medications, and underlying diseases as contributors to the dysphonia. The patient was diagnosed with HiDAC-induced dysphonia. This toxic effect was self-limiting, and the patient recovered in 10–15 days. Chemotherapy-induced dysphonia is a rarely reported and easily overlooked side effect. This adverse reaction is typically temporary and non-life-threatening; however, it substantially diminishes quality of life and may occasionally necessitate the discontinuation or postponement of chemotherapy. Physicians should be aware of this complication when administering chemotherapeutic agents.